2020
DOI: 10.1080/0886022x.2019.1707097
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microwave ablation treatments in patients with renal secondary and primary hyperparathyroidism

Abstract: Purpose: Microwave ablation (MWA) is feasible for severe renal secondary hyperparathyroidism (SHPT) and primary hyperparathyroidism (PHPT) patients ineligible for parathyroidectomy (PTX).Here we compared the clinical manifestations and characteristics of parathyroid glands in these two groups, and summarized the techniques, safety and efficacy of MWA. Methods: Baseline clinical characteristics, ablation-related techniques, adverse events/complications, and efficacy were recorded. Results: In SHPT group, malnut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
1
11
0
2
Order By: Relevance
“…Parathyroidectomy (PTX) is considered when patients develop drug resistance or side effects [317]. Recent studies also confirmed the feasibility and efficacy of microwave ablation treatment for patients ineligible for PTX [318,319]. Therefore, more studies are warranted to evaluate whether there is an additional benefit of adding estrogen or SERMs to the established treatment regimen.…”
Section: Chronic Kidney Disease-mineral and Bone Disorder (Ckd-mbd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Parathyroidectomy (PTX) is considered when patients develop drug resistance or side effects [317]. Recent studies also confirmed the feasibility and efficacy of microwave ablation treatment for patients ineligible for PTX [318,319]. Therefore, more studies are warranted to evaluate whether there is an additional benefit of adding estrogen or SERMs to the established treatment regimen.…”
Section: Chronic Kidney Disease-mineral and Bone Disorder (Ckd-mbd)mentioning
confidence: 99%
“…Potential etiologies include platelet dysfunction, dysfunctional von Willebrand factor, decreased production of thromboxane, uremic toxins, and anemia [322,323]. The bleeding tendency in uremic patients was further complicated or exacerbated by their comorbidities and medications (e.g., hypertension, atrial fibrillation with warfarin therapy, cerebrovascular disease with anticoagulants) [318,[324][325][326]. For patients who were refractory to routine interventions for uremic bleeding, conjugated estrogens might be another option [327][328][329].…”
Section: Uremic Coagulopathymentioning
confidence: 99%
“…It can also lead to small local lesions and a large systemic effect 7 . Patients with PHPT usually develop hypercalcemia 5 . Its main clinical manifestations are complex, with kidney stones being the most common.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Moreover, the incidence of PHPT in women is three times higher than that in men, and the incidence increases with age. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation